An enigma of a country human dignity and utopic society - Dewantara, Jagad Aditya; Syofianti, Resti; Arifiyanti, Fitria (Universitas Negeri Yogyakarta, 2022)
This paper to provide an explanation of the ideology that fights for human dignity and the formation of an imaginary or utopian society. The ideology adopted is the political ideology of anarchism and liberalism which both fight for equal rights and freedom. The two ideologies do have different histories or intricacies, but in this paper they will become a tool for human beings living in a country to maintain their dignity as owners of the right to life. And also the formation of an ideal that is often referred to as a utopia or an imaginary society in the midst of the development of increasingly advanced science and technology. The state is an enigma or a mystery. One of the mysteries is human dignity and utopian society which will be raised in this paper